Three-phase induction motor control using scalar control method based on the Internet of Things (IoT) - Rahma Putri, Nadila; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
The induction motor is one of the most widely used types of electric motors in the industrial sector due to its simple structure and high reliability. However, speed control of induction motors often requires an advanced control system to ensure both efficiency and flexibility. This final project presents the design and implementation of a three-phase induction motor control system using the scalar control method (V/f), integrated with Internet of Things (IoT) technology. The system enables users to monitor and control the motor’s frequency and direction of rotation in real-time through a web-based interface developed using Node-RED. The system design involves the integration of hardware components, including a three-phase induction motor, an Omron 3G3JX-A Variable Speed Drive (VSD), and an Omron CP2E-N Programmable Logic Controller (PLC), which communicate using the Modbus RTU protocol. The PLC is programmed using CX-Programmer to implement the appropriate control logic, while the IoT interface enables users to send commands and monitor operational data remotely. Test results indicate that the system is capable of regulating motor speed linearly in response to input frequency without causing current surges, and it provides accurate, real-time motor parameter data through the dashboard interface.